Automatic Generation of Index Phrases for Document Retrieval Using Semantic and Syntactic Information - van Bommel, Martin; Schuegraf, Ernst J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF